Paclitaxel-Loaded, Pegylated Carboxylic Graphene Oxide with High Colloidal Stability, Sustained, pH-Responsive Release and Strong Anticancer Effects on Lung Cancer A549 Cell Line - Athina Angelopoulou; Myria Papachristodoulou; Efstathia Voulgari; Andreas Mouikis; Panagiota Zygouri; Dimitrios P. Gournis; Konstantinos Avgoustakis (MDPI AG, 2024)
Background: Graphene Oxide (GO) has shown great potential in biomedical applications for cancer therapeutics. The biosafety and stability issues of GO in biological media have been addressed by functionalization with polyethylene glycol (PEG). Methods: In this work, carboxylated, nanosized GO (nCGO) was evaluated as a potential carrier of paclitaxel (PCT). The effect of PEG characteristics on particle size and surface charge, colloidal stability, drug, and release, and the hemolytic potential of nCGO, was investigated. Optimum PEG-nCGO/PCT formulations based on the above properties were evaluated for their anticancer activity (cytotoxicity and apoptosis induction) in the A549 lung cancer cell line. Results: An increase in the length of linear PEG chains and the use of branched (4-arm) instead of linear PEG resulted in a decrease in hydrodynamic diameter and an increase in ζ potential of the pegylated nCGO particles. Pegylated nCGO exhibited high colloidal stability in phosphate-buffered saline and in cell culture media and low hemolytic effect, even at a relatively high concentration of 1 mg/mL. The molecular weight of PEG and branching adversely affected PCT loading. An increased rate of PCT release at an acidic pH of 6.0 compared to the physiological pH of 7.4 was observed with all types of pegylated nCGO/PCT. Pegylated nCGO exhibited lower cytotoxicity and apoptotic activity than non-pegylated nCGO. Cellular uptake of pegylated nCGO increased with incubation time with cells leading to increased cytotoxicity of PEG-nCGO/PCT with incubation time, which became higher than that of free PCT at 24 and 48 h of incubation. Conclusions: The increased biocompatibility of the pegylated nCGO and the enhanced anticancer activity of PEG-nCGO/PCT compared to free PCT are desirable properties with regard to the potential clinical application of PEG-nCGO/PCT as an anticancer nanomedicine.